Detritus and microbial ecology in aquaculture. Proc. conference on detrital systems for aquaculture on 26-31 August 1985, in Bellagio Como, Italy. - Moriarty, D.J.W. and Pullin, R.S.V. (ed.). (Manila, Philippines ICLARM, 1987)
ICLARM Conference Proceedings 14
Keywords: Detritus; Food chain; Aquaculture; Microbial ecology